Formulasi dan uji aktivitas antioksidan sediaan sheet mask dari sari buah lemon cui (Citrus microcarpha B.) sebagai anti-aging - Arifin, Arfiani; Nada, Salsabila Yudratun; Mawarni, Razifah Suci; Adi, Abdul Vashar (Sasambo Journal of Pharmacy, 2024)
Lemon cui (Citrus microcarpa Bunge.), also known as fish lemon or kalamansi lemon, is a local citrus that mainly grows in North Sulawesi. This study aims to determine the IC50 value of lemon cui juice and develop "Lemon cui" juice sheet mask formulations that meet physical quality test standards. Samples of "lemon cui" fruit juice were obtained by adding enough water and then separating the pulp to extract the juice. The sheet mask preparation formulation involved varying the concentration of the lemon cui fruit juice lyophilisate sample, including F1 (0.5%), F2 (1%), F3 (1.5%), and a negative control (without lyophilisate of lemon cui fruit juice). The physical quality testing encompasses organoleptic, homogeneity, pH, and irritation assessments. The results of physical quality testing for F1, F2, F3, and the negative control have met the requirements of the physical quality test. The antioxidant test results showed that the antioxidant activity in lemon juice lyophilisate and sheet mask essences F2 and F3 fell into the very strong antioxidant category, while sheet mask essence F1 was classified as a strong antioxidant.